Adverse Reactions to Antiretrovirals in Cuban Patients Living with HIV/AIDS. - Morales-Pérez, Mayasil (MEDICC Review, 2021)
INTRODUCTION Disease and deaths from HIV/AIDS have decreased since antiretroviral treatment was introduced in 1996. Since 2005, as treatment availability has increased worldwide, deaths from HIV/AIDS have declined 48%. As of November 2019, 26,952 cases have been reported in Cuba, of which 5159 (19.1%) are deceased. The country has experienced a reduction in mortality rates since 2002, when antiretroviral treatment became available. Although there are clearly benefits to treatment, it is important to understand antiretroviral safety profiles as their toxicity may lower treatment adherence. OBJECTIVE Describe adverse reactions attributable to antiretrovirals used in Cuban patients living with HIV/AIDS. METHODS I studied notifications of adverse reactions to antiretro-virals used in Cuban patients with HIV/AIDS from January 2003 to December 2017. The sample consisted of 352 notifications in the National Pharmacovigilance Database regarding adverse reactions attributed to antiretrovirals. The variables considered were sex, notification year, antiretroviral drug, and number, type, frequency and severity of adverse reactions, whether or not they were preventable, and the reasons for categorizing them as they were. RESULTS Antiretrovirals reported an average adverse reaction rate of 2.1 per million population per year, representing 24.2% of adverse reactions produced by the antiviral drug group in that period. Adult males represented 75% (264/352) of patients who had adverse reactions to antiretrovirals. Most adverse reactions were in response to nevirapine (29.0%; 102/352) and zidovudine (26.7%; 94/352). The most frequent reactions were hypersensitivity (24.4%; 86/352), digestive disorders (15.9%; 56/352) and anemia (15.6%; 55/352). Reactions were common (62.5%; 220/352) and moderate in severity (70.4%; 248/352). Preventable reactions made up 52.6% (185/352) of adverse reactions. Of preventable reactions, 68.1% (126/185) were associated with drug interactions and 16.2% (30/185) with improper dosage or prescription errors. CONCLUSIONS Adverse reactions to antiretrovirals in Cuban patients are common and moderate in severity. The drug with the most notifications was nevirapine, and the most common adverse reaction was hypersensitivity. More than half of adverse reactions are considered preventable, and their main causes are prescription errors.